Case report: A large gastric calcifying fibrous tumor treated with endoscopic submucosal excavation - Zhong, Ziyou; Li, Zhenguo; Xing, Yufeng; Guo, Shaoju (Frontiers in Oncology, 2024)
Gastric calcifying fibrous tumor (CFT) is a rare benign mesenchymal tumor. Several previous studies have reported surgical resection for gastric CFT larger than 20mm for the difficulty in preoperative diagnosis. Here, we report a rare case of large gastric CFT treated with endoscopic submucosal excavation (ESE). A 70-year-old woman presented with recurrent epigastric pain and underwent endoscopy, which revealed a 35mm-sized submucosal tumor in the gastric body. ESE was performed after imaging examination and endoscopic ultrasonography. En bloc resection was achieved, but due to the specimen's substantial size and difficulty in mincing, it posed challenges for removal through the mouth. Finally, the specimen was temporarily placed in the stomach and was completely removed two days later. The diagnosis was confirmed based on pathological and immunohistochemical findings. There was no recurrence during the patient's 11-month follow-up. We provided a case report related to the diagnosis and endoscopic treatment for large gastric CFT. In addition, our experience of temporarily leaving a large postoperative specimen, considered a benign lesion, in the stomach for later removal was successful but requires appropriate timing to avoid blockage of the gastrointestinal tract.